2014
DOI: 10.1002/2013wr014155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic streambed fluxes during rainfall‐runoff events

Abstract: Observed 3-D temperature distributions within a streambed were used to analyze the effects on exchange fluxes between groundwater and the stream during rainfall-runoff events. By combining a dense vertical and lateral monitoring network of streambed temperatures with coupled surface/subsurface 3-D flow and heat transport modeling, we demonstrate how temperature can be used directly as a calibration target. Three model setups with different hydraulic conductivity distributions were evaluated in an optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 39 publications
2
50
1
Order By: Relevance
“…Weaker groundwater gradients could potentially allow for a temporarily weakening of the groundwater discharge to the stream during large rain events, entailing a temporary dominance of surface and event water. Similar mechanisms were observed by Karan et al (2014) where large rain events temporarily decreased groundwater discharge to Holtum stream. Also Gerecht et al (2011) observed highly dynamic responses to rapid stage changes in terms of shifting between gaining and losing conditions in a groundwater influenced river.…”
Section: Temporal Dynamics and Catchment-scale Differences In Runoff supporting
confidence: 77%
“…Weaker groundwater gradients could potentially allow for a temporarily weakening of the groundwater discharge to the stream during large rain events, entailing a temporary dominance of surface and event water. Similar mechanisms were observed by Karan et al (2014) where large rain events temporarily decreased groundwater discharge to Holtum stream. Also Gerecht et al (2011) observed highly dynamic responses to rapid stage changes in terms of shifting between gaining and losing conditions in a groundwater influenced river.…”
Section: Temporal Dynamics and Catchment-scale Differences In Runoff supporting
confidence: 77%
“…D. H. Käser et al [] provided a detailed description of many aspects of streambed structure, including hydraulic conductivity, gradient, topography, and exchange fluxes. Other noteworthy examples are Karan et al [], who measured hydraulic conductivity, temperature profiles, and hydraulic gradients at a large number of locations along the Holtum stream in Denmark. Rosenberry and Pitlick [] measured vertical and horizontal hydraulic conductivities, seepage rates, hydraulic gradients, and shear stress and related their results to the bedforms present.…”
Section: Advances In Characterizing the Physical Environment Of Rivermentioning
confidence: 99%
“…Temporally evolving physical features, such as meander bends, bar forms, pool‐riffle sequences [ Käser , ; Tonina and Buffington , ], and highly transient ripples and moving bedforms [ Käser et al ., ] grow and shrink at multiple temporal and spatial scales. This continually evolving porous medium imparts nested hyporheic‐scale exchange superimposed on longer flowpaths that confounds determination of larger‐scale distribution of groundwater discharge to a stream or river [ González‐Pinzón et al ., ; Hatch et al ., ; Karan et al ., ; Menció et al ., ; Rosenberry and Pitlick , ]. In addition to diffuse groundwater discharge controlled by reach‐scale hydraulic gradients and geologic properties, groundwater discharge also is focused in discrete areas where flow is orders of magnitude faster than diffuse flow [ Hare et al ., ; Kidmose et al ., ].…”
Section: Introductionmentioning
confidence: 99%